Smart Secured Real Time Agriculture Monitoring System - Srirampavan, J (International Journal of Engineering and Technology, 2018)
Embedded systems in Agriculture play a vital role in unifying the work involved and improve conservations. Designing a smart as well as a cost efficient and more user-friendly system will be idealistic challenge. The following system that has been proposed is designed with those ideal constraints in mind. It consists of a Raspberry pi3 as a gateway that links the sensor networks with the cloud. To improve security an MQTT protocol is used for cloud connectivity. The communication between the sensor networks is managed by NRF24L01. The Sensor network is a separate entity that can used like a plug and play device and is built by a micro controller with a LCD display and an interfaced GPS. Multicasting is also possible between sensor networks and the gateway. The processed data from the sensor networks is sent through NRF24L01 to the gateway. The gateway further processes and encapsulates the data and through MQTT the data gets stored on the cloud. This cloud data can be accessed through computer or mobile deviceÂ Â